Agglomerative Clustering of 2022 Earthquakes in North Sulawesi, Indonesia: Author's Country: Indonesia (Information System; Universitas Buana Perjuangan Karawang, 2023)
This paper presents a cluster analysis of earthquake data in the surrounding region of North Sulawesi, Indonesia. The dataset comprises seismic data recorded throughout the year 2022, obtained from the BMKG earthquake repository. A total of 211 earthquakes were included in the analysis, with a minimum magnitude threshold of 2.5 and a maximum depth of 300 km. The agglomerative clustering technique, combined with the elbow method, was employed to determine the optimal and distinct number of clusters. As a result, four unique clusters were identified. Cluster 1 exhibited high magnitudes, with an average magnitude of 4.4, and shallow depths, averaging at 20 km. Cluster 2 also had high magnitudes, averaging at 4.4, but deeper depths, with an average of 199 km. Cluster 3 consisted of earthquakes with low magnitudes, averaging at 3.4, and shallow depths, averaging at 21 km. Lastly, Cluster 4 comprised earthquakes with low magnitudes, averaging at 3.4, but deeper depths, with an average of 136 km. Among the 211 earthquakes, 29 were assigned to Cluster 1, 39 to Cluster 2, 100 to Cluster 3, which had the highest population, and 43 to Cluster 4. This study provides valuable insights into the clustering patterns and characteristics of earthquakes in the region, contributing to a better understanding of seismic activity in North Sulawesi, Indonesia